2019
DOI: 10.1007/s10597-018-00364-7
|View full text |Cite
|
Sign up to set email alerts
|

PTSD Symptoms, Vicarious Traumatization, and Burnout in Front Line Workers in the Homeless Sector

Abstract: Work with clients who have trauma-related problems is reported to lead to a constellation of reactions including vicarious traumatization, compassion fatigue, and burnout. Traumatic experiences are ubiquitous in the lives of homeless people, stemming from multiple life events prior to, and as a result of, experiencing homelessness. While most studies examine either burnout and vicarious traumatization or potential PTSD in people who work with those who are traumatized, they generally do not look at the possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 37 publications
3
52
0
Order By: Relevance
“…The long-term psychological effects named were depressive states and symptoms of burnout. Previous studies had already described a high prevalence of mental illness and burnout among this professional group [21,45]. The prevalence of depression, however, was not significantly different to that of the general population [18].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The long-term psychological effects named were depressive states and symptoms of burnout. Previous studies had already described a high prevalence of mental illness and burnout among this professional group [21,45]. The prevalence of depression, however, was not significantly different to that of the general population [18].…”
Section: Discussionmentioning
confidence: 68%
“…That said, conclusive information in available literature is still scarce and in some cases inconsistent [16]. Among workers in refugee and homeless aid, secondary trauma is also frequently observed due to being confronted with clients’ traumatic experiences [17,21,22]. In this connection, no findings are available in this study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…According to Waegemakers-Schiff and Lane, elevated levels of burnout and vicarious traumatization were found in almost a quarter of a sample of workers in homeless aid. Additionally, high rates of traumatic stress were described [23]. There have been reports of higher stress levels for female social workers [4] as well as more severe symptoms of depression for female aid workers [21].…”
Section: Introductionmentioning
confidence: 99%
“…Staff in our study reported experiences of vicarious trauma which can be defined as being continually exposed both to traumatic situations, and to those who are traumatized, with consequent negative impact (Baird & Kracen, 2006). The impact of helping individuals who have experienced homelessness and wider adverse events can lead to the development of elevated rates of a combination of burnout, compassion fatigue, vicarious traumatization, and post-traumatic stress in key workers (Arslan, 2013;Seager, 2013;Waegemakers Schiff & Lane, 2019). Burnout has also been noted in evaluations of the Canadian At Home/Chez Soi HF program (Macnaughton et al, 2015).…”
Section: Discussionmentioning
confidence: 91%